Pemodelan Migrasi Tenaga Kerja Terinduksi Modal untuk Konvergensi Regional Indonesia - Dina Rahma Wita; Muhammad Subhan (Politeknik Negeri Batam, 2026)
Regional inequality in Indonesia presents a persistent structural challenge characterized by capital concentration and labor agglomeration in core regions. Conventional models often fail to capture the endogenous feedback between capital accumulation, dynamic labor migration, and regional ecological limits. To address this theoretical gap, we formulate a four-dimensional non-linear ordinary differential equation (ODE) system integrating the Solow neoclassical growth framework, logistic population dynamics bounded by regional carrying capacities (κ), and Capital-Induced Labor Migration (CILM). The model is empirically calibrated using Statistics Indonesia macroeconomic data (2020-2024), classifying regions into Core and Periphery based on a strict 2.63% Gross Regional Domestic Product (GRDP) equal-distribution threshold. Analytical validity is rigorously established through mathematical proofs of Positive Invariance and Ultimate Boundedness. Numerical simulations using the Runge-Kutta 4th Order method reveal a critical phenomenon termed